Low-power internet of things with NDN & cooperative caching - Oliver Hahm and Emmanuel Baccelli and Thomas C. Schmidt and Matthias Wählisch and Cedric Adjih and Laurent Massoulie (Association for Computing Machinery (ACM), 2017)
Energy efficiency is a major driving factor in the Internet of Things (IoT). In this context, an IoT approach based on Information-Centric Networking (ICN) offers prospects for low energy consumption. Indeed, ICN can provide local in-network content caching so that relevant IoT content remains available at any time while devices are in deep-sleep mode most of the time. In this paper, we evaluate NDN enhanced with CoCa, a simple side protocol we designed to exploit content names together with smart interplay between cooperative caching and power-save sleep capabilities on IoT devices. We perform extensive, large scale experiments on real hardware with IoT networks comprising of up to 240 nodes, and on an emulator with up to 1000 nodes. We show in practice that, with NDN+CoCa, devices can reduce energy consumption by an order of magnitude while maintaining recent IoT content availability above 90~%. We furthermore provide auto-configuration mechanisms enabling practical ICN deployments on IoT networks of arbitrary size with NDN+CoCa. With such mechanisms, each device can autonomously configure names and auto-tune parameters to reduce energy consumption as demonstrated in this paper.
Keywords: Information-centric networking; energy efficiency; cooperative caching